Revolusi Digital dan Strategi Bisnis “Tinjauan Terkini terhadap Pertumbuhan Ekonomi” - Hasan, Hasan; Arfah, Hj Aryati; Arifin, Arifin (Program Pascasarjana STIE Amkop Makassar, 2024)
In an ever-evolving digital age, technological transformation has become a key driver of change in the global economic landscape. This research investigates the linkage between economic growth and business strategy in the digital era, taking into account the impact of digital technology on various economic sectors. Through in-depth analysis, this article outlines fundamental changes in consumer behavior, production patterns, and business strategies that have emerged along with technological advancements. We highlight the importance of adaptation and innovation in the face of the challenges presented by the digital age, taking into account the use of data and analytics, digital transformation, and digital platform integration. This review provides valuable insights for business practitioners, policymakers, and academics to understand the complex dynamics involved in managing a business in an ever-changing digital age, as well as to design relevant and effective strategies in achieving long-term growth and success. Keywords: Economic growth, Digital era, Business strategy, Technology transformation, Digital transformation